Chains - Anderson, Laurie Halse (New York : Simon & Schuster Books for Young Readers, 2008)
After being sold to a cruel couple in New York City, a slave named Isabel spies for the rebels during the Revolutionary War.
Sequel: Forge.
Ages 10 up.
Keywords: Slavery -- Fiction; African Americans -- Fiction; Spies -- Fiction; New York (N.Y.) -- Fiction -- History -- 19th century; United States -- Fiction -- History -- 1775-1783, Revolution